The factors affecting student satisfaction with online education during the COVID-19 pandemic: an empirical study of an emerging Muslim country. Issue 3 (14th December 2020) - Basuony, Mohamed A.K.; EmadEldeen, Rehab; Farghaly, Marwa; El-Bassiouny, Noha; Mohamed, Ehab K.A.
Abstract : Purpose: This study aims to investigate factors affecting students' satisfaction with online learning during the COVID-19 pandemic. Design/methodology/approach: This study uses quantitative data. A survey of 280 respondents, representing undergraduate students in business schools in Cairo, Egypt is conducted. The survey includes both public and private universities. The participants are questioned about their opinions and attitudes toward satisfaction with online learning amidst the COVID-19 pandemic. Findings: The findings of this study reveal that Egyptian university students prefer to use synchronous teaching methods using different platforms. Attending virtual sessions and real-time conference call classes are the most preferred mode of delivery as perceived by the respondents. Also, the results of this study found that the internet, platform, class time, loss of interest, motivation and self-motivation and use of online exams as an assessment can be considered as the factors that significantly affect students' satisfaction with online learning in Egypt. Originality/value: To the best of the knowledge, this study is among the first group of studies in Muslim emerging countries that explore the factors affecting students' satisfaction with online learning during the COVID-19 pandemic.